Dynamic ocean management: Defining and conceptualizing real-time management of the ocean. (August 2015) - Maxwell, Sara M.; Hazen, Elliott L.; Lewison, Rebecca L.; Dunn, Daniel C.; Bailey, Helen; Bograd, Steven J.; Briscoe, Dana K.; Fossette, Sabrina; Hobday, Alistair J.; Bennett, Meredith; Benson, Scott; Caldwell, Margaret R.; et al.
Abstract: Most spatial marine management techniques (e.g., marine protected areas) draw stationary boundaries around often mobile marine features, animals, or resource users. While these approaches can work for relatively stationary marine resources, to be most effective marine management must be as fluid in space and time as the resources and users we aim to manage. Instead, a shift towards dynamic ocean management is suggested, defined as management that rapidly changes in space and time in response to changes in the ocean and its users through the integration of near real-time biological, oceanographic, social and/or economic data. Dynamic management can refine the temporal and spatial scale of managed areas, thereby better balancing ecological and economic objectives. Temperature dependent habitat of a hypothetical mobile marine species was simulated to show the efficiency of dynamic management, finding that 82.0 to 34.2 percent less area needed to be managed using a dynamic approach. Dynamic management further complements existing management by increasing the speed at which decisions are implemented using predefined protocols. With advances in data collection and sharing, particularly in remote sensing, animal tracking, and mobile technology, managers are poised to apply dynamic management across numerous marine sectors. Existing examples demonstrate that dynamic management can successfully allow managers to respond rapidly to changes on-the-water, however to implement dynamic ocean management widely, several gaps must be filled. These include enhancing legal instruments, incorporating ecological and socioeconomic considerations simultaneously, developing 'out-of-the-box' platforms to serve dynamic management data to users, and developing applications broadly across additional marine resource sectors. Highlights: Marine management follows terrestrial management but oceans are more dynamic. Marine management must be as fluid in space and time as resources and users managed. Dynamic management rapidly changes in space and time like marine species, habitats, users. Dynamic management can refine the temporal and spatial scale of managed areas. Integrate dynamic management with existing management such as adaptive management.